Analysis of Various Difficulties in Learning English Subjects - zelika amalia; Evi Rosmiyati; M. Ali Akbar Zam (IKIP PGRI Pontianak, 2023)
The aims of this study were to: (1) describe the difficulty of learning English in class X MA Muhammadiyah 01 Palembang in the 2022 academic year. This type of research was qualitative with questionnaires, observations, and questions from the researcher. Research data analysis was carried out in three ways, namely data reduction, data presentation, questionnaire, conclusion drawing and verification. The subjects of this study were students of class X IPA/IPS, totaling 36 students. The data collection in this study used a scale of English learning difficulties which amounted to 25 valid items. The scale is based on the criteria for learning English difficulties, namely: (1) Lazy to learn English, (2) Lack of understanding of the material given by the teacher, (3) Difficulty pronouncing English words, (4) Difficulty expressing opinions. while learning English, (5) Difficulty concentrating when learning English. The results of this study indicate that: There is the highest data from learning outcomes, which is about 33 (91%) students choose the opinion